Perioperative von Willebrand factor dynamics are associated with liver regeneration and predict outcome after liver resection. Issue 4 (27th February 2018) - Starlinger, Patrick; Pereyra, David; Haegele, Stefanie; Braeuer, Paul; Oehlberger, Lukas; Primavesi, Florian; Kohler, Andreas; Offensperger, Florian; Reiberger, Thomas; Ferlitsch, Arnulf; Messner, Barbara; Beldi, Guido; et al.
Abstract : von Willebrand Factor (vWF) was found to mediate platelet influx during the early phase of liver regeneration in mice. Furthermore, increased vWF‐antigen (vWF‐Ag) levels were shown to be predictive for outcome of patients with chronic liver disease. Accordingly, we aimed to assess the relevance of perioperative vWF‐Ag dynamics in terms of liver regeneration and clinical outcome in patients undergoing liver resection (LR). Accordingly, we observed that vWF‐Ag and its activity—estimated by ristocetin cofactor measurement—increased immediately after induction of liver regeneration and was associated with platelet accumulation within the liver. However, a significant vWF‐Ag burst was only observed in patients with unaffected postoperative liver regeneration. E‐selectin, as an established marker for endothelial cell activation, was found to correlate with vWF‐Ag in the liver vein after induction of liver regeneration (R = 0.535, P  = 0.022). Preoperative vWF‐Ag levels significantly predicted postoperative liver dysfunction (LD; N = 95; area under the curve, 0.725; P  = 0.009). Furthermore, a cutoff of vWF‐Ag ≥182% was defined to identify patients with a higher risk for postoperative LD or morbidity. This was confirmed within an independent mulitcenter validation cohort (N = 133). Ultimately, multivariable analysis revealed that vWF‐Ag was an independent predictor of postoperative LD and morbidity. Conclusion : Within this study, we were able to provide evidence that an initial vWF burst is required to allow for adequate platelet accumulation and concomitant liver regeneration post‐LR and might be abolished as a consequence of intrahepatic endothelial cell dysfunction. We were further able to reveal and validate the potential of preoperative vWF‐antigen levels to predict poor postoperative outcome in patients undergoing LR. Despite the pathophysiological relevance of our findings, vWF‐Ag seems to be a valuable tool for preoperative risk assessment in patients undergoing LR. (Hepatology 2018;67:1516‐1530)